The Mediating Effect of Well-Being on the Relationship Between Leadership Capacity and Teaching Effectiveness: A Convergent Design - V. Balbacal, Cherry Lyn; B. Dayaganon, Avee Joy (The Future of Education Journal, 2025)
This study determined the mediating effect of well-being on the relationship between leadership capacity and teaching effectiveness of teachers in public elementary school in Region XI, Philippines. This study utilized mixed methods research particularly convergent design. In the quantitative phase, adapted and validated survey questionnaires were employed while an interview guide was utilized in the qualitative phase during in-depth interview IDI and focus group discussion FGD. The statistical tools used in analyzing the quantitative data included mean, standard deviation, and multiple linear regression analysis while thematic analysis was used for the qualitative data. The results revealed that the status of well-being, leadership capacity, and teaching effectiveness of school heads were rated very high. There is a significant relationship between leadership capacity and teaching effectiveness. The present study found support for well-being as a mediator in the leadership capacity and teaching effectiveness. Therefore, public elementary school teachers must focus on how to function effectively to cope adequately to execute in the school, the partial mediation effect of well-being indicates a strong link. Furthermore, the themes generated from the role of experiences that shaped their beliefs included student-centered teaching and reflective teaching practices. Likewise, empathy and patience, and resilience and dedication were the themes generated from the experiences that shaped their attitude. The themes that surfaced from the experiences that shaped the commitment of teachers involved lifelong learning and improvement, and student success and well-being. The nature of data integration revealed merging-converging and merging-expansion.